Synthesis and Characterization of New-2,3-Disubstituted Quinazolinone Derivatives as Antibacterial Agents - Lfta, Souad J; Ayram, Nabeel B; Baqer, Salah M (Al-Nahrain Journal of Science, 2016)
In this work, some new 2,3-disubsituted quinazolinone derivatives were synthesized. The reaction of substituted anthranilic acid with 3-chlorophenylisothiocyanate gave the compounds [3-(3-chlorophenyl)-2-mercaptoquinazoline-4(3H)-one] (1a,b). compounds (1a,b) where treated with chloroethylacetate in presence of potassium carbonate gave the compounds [-4-oxo-3,4-dihydroquinazoline-2-yl)thio)acetate] (2a,b). Reaction with hydrazine hydrate afforded the acetohydrazides [-4-oxo-3,4-dihydroquinazoline-2-yl) thio) acetohydrazide](3a,b). The acetoohydrazides (3a,b) were treated with aromatic aldehydes to give the Schiff’s bases [-Nˉ-(3-nitrobenzylidene)acetohydrazide] (5a,b). Treatment of derivatives (1a,b) with hydrazine hydrate afforded the hydrazine derivatives [-2-hydrazinylquinazoilne-4(3H)-one] (4a,b) which also used in synthesizing Schiff’s bases [(E)(2-(3-nitrobenzyllidene)hydrazinyl)] (6a,b). Alkyl halide was treated with compounds (1a,b) in presence acetone to give of [-2-(methylthio)quinazoline-4(3H)-one] (7a,b), and with arylhalide in DMF gave the compounds [-2-((4-nitrophenyl)thio)quinazoline-4(3H)-one)] (8a,b). The structures of all prepared compounds have been elucidated using FTIR,1 HNMR, and MASS spectroscopy. The antibacterial activity was evaluated for (1,5,6,7)a-b derivatives.